The green house effect. - Lim, Marie Shimin. (2012)
The Green House Effect is a feature writing project about green buildings in Singapore. It explores the rising popularity of environmentally friendly buildings and the impact it would have on Singaporeans in terms of energy savings and protection from the effects of global warming.